Human Crossfeed in Dual-Axis Manual Control with Motion Feedback. Issue 19 (2016) - Barendswaard, S.; Pool, D.M.; Mulder, M.
Abstract: While many realistic manual control tasks require human operators to control multiple degrees-of-freedomsimultaneously, our understanding of such multi-axis manual control has not moved far beyond considering it simply as the control of multiple fully-independent axes. This investigation aims to further our understanding of multi-axis control by focusing on one phenomenon that is known to occur in such tasks: crossfeed. Crossfeed occurs when operators' inputs in one controlled axis feed into another controlled degree-of-freedom, thereby affecting overall control performance. A human-in-the-loop experiment, in which operators performed a dual-axis aircraft roll and pitch tracking task with physical motion feedback, was conducted in the SIMONA Research Simulator at TU Delft. Three conditions were tested: the full dual-axis control task, supplemented with reference single-axis roll and pitch tasks. Through the use of independent target and disturbance forcing function signals in both controlled axes, we were able to detect the presence of crossfeed in this dual-axis task from spectral analysis. Furthermore, these signals facilitated the objective identification of the dynamics of the crossfeed contribution, in parallel with estimating operators visual and motion responses. The crossfeed dynamics were found to resemble the well-known dynamics of human operators' visual responses. The crossfeed contribution was found to explain up to 20% of the measured control inputs, thereby indicating that crossfeed can be a factor of significance in multi-axis manual control.